2001
DOI: 10.1046/j.0953-816x.2001.01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic control of synaptic plasticity in the dorsal striatum

Abstract: Cortical glutamatergic and nigral dopaminergic afferents impinge on projection spiny neurons of the striatum, providing the most significant inputs to this structure. Isolated activation of glutamate or dopamine (DA) receptors produces short-term effects on striatal neurons, whereas the combined stimulation of both glutamate and DA receptors is able to induce long-lasting modifications of synaptic excitability. Repetitive stimulation of corticostriatal fibres causes a massive release of both glutamate and DA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
246
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(266 citation statements)
references
References 67 publications
18
246
1
1
Order By: Relevance
“…The endocannabinoid-dependent inhibition of GABA inputs might favor synaptic plasticity at excitatory corticostriatal synapses by enhancing the level of postsynaptic depolarization required for the induction of both LTP and LTD (Centonze et al, 2001). In this line, it has recently been shown that cannabinoid-dependent inhibition of GABA transmission may actually facilitate the emergence of synaptic plasticity at excitatory synapses in the hippocampus (Carlson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The endocannabinoid-dependent inhibition of GABA inputs might favor synaptic plasticity at excitatory corticostriatal synapses by enhancing the level of postsynaptic depolarization required for the induction of both LTP and LTD (Centonze et al, 2001). In this line, it has recently been shown that cannabinoid-dependent inhibition of GABA transmission may actually facilitate the emergence of synaptic plasticity at excitatory synapses in the hippocampus (Carlson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, long-term potentiation (LTP) and long-term depression (LTD) induced by high-frequency stimulation are forms of synaptic plasticity that have long been considered candidate processes for learning and memory. Acute high-frequency activation of cortical inputs is well known to produce LTP or LTD at the corticostriatal synapse (Calabresi et al, 1996;Centonze et al, 2001;Reynolds and Wickens, 2002;Gerdeman et al, 2003;Mahon et al, 2004), and such effects have been implicated in altered gene induction after psychostimulant treatments (Graybiel et al, 2000). Importantly, there is evidence that, in vivo, lowfrequency stimulation can be sufficient to induce LTP (Charpier et al, 1999).…”
Section: Gene Regulation Enabling Motor Memory Formation: a Hypothesismentioning
confidence: 99%
“…Importantly, there is evidence that, in vivo, lowfrequency stimulation can be sufficient to induce LTP (Charpier et al, 1999). Both LTP and LTD are dependent on dopamine input (Calabresi et al, 1996;Centonze et al, 2001;Reynolds and Wickens, 2002), with low dopamine levels apparently favoring LTD and high dopamine levels producing LTP at the corticostriatal synapse (Reynolds and Wickens, 2002). Notably, such LTP is blocked by D1 receptor antagonism (Kerr and Wickens, 2001;Reynolds et al, 2001;Centonze et al, 2003).…”
Section: Gene Regulation Enabling Motor Memory Formation: a Hypothesismentioning
confidence: 99%
“…If reinforcement involves long-term modifications in the strength of striatal input signals [9,102,124], then abnormalities in the relative strength of these inputs would prevent reinforcement of appropriate inputs. However, DA is also necessary for striatal plasticity [21,25]. DA's role in learning is, therefore, likely to include not only a selective gate-keeping function for glutamate inputs, but also a direct role in promoting plasticity of currently active synapses.…”
Section: Da Activity Gates the Throughput Of Sensorimotor And Incentimentioning
confidence: 99%